DEVELOPING COMMUNICATIVE SKILLS IN ENGLISH AMONG NON-PHILOLOGICAL STUDENTS BASED ON ARTIFICIAL INTELLIGENCE TECHNOLOGIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the era of digital transformation, artificial intelligence (AI) technologies offer innovative tools for enhancing English communicative competence, especially among non-philological students who often lack linguistic training. This study explores the integration of AI-powered platforms such as chatbots, virtual assistants, and adaptive methods for fostering speaking, listening, and writing skills through interactive and personalized experiences. Emphasis is placed on motivation, engagement, and realtime feedback, which collectively contribute to more effective language acquisition.